Efektivitas Sterilisasi Media NA dan PDA Pada Kegiatan Praktikum Mikrobiologi Penyamakan Kulit - Armila Zahra Tawarniate; Wijayanti (UIN Sunan Kalijaga Yogyakarta, 2023)
Microbiology practicum activities in tannery process are carried out to determine the causes of leather’s damage caused by microbial activity. This practicum are carried out using media. Practicum activities can be disrupted due to obstructed observations because of bacterial and fungal contamination from the environment. Bacterial and fungal contamination can occur due to sub-optimal media sterilization or improper media storage. The purpose of this study was to determine the effectiveness of the sterilization technique using autoclaves and UV irradiation on NA and PDA media which are often used. The results showed that the media sterilization technique with an autoclave tended to be more effective than UV light sterilization although it did not provide a significant difference. Media without sterilization gives better results. It can be caused by the heating process up to 100 ˚C when making the media. This process can kill most of the microbes present in the liquid media.